Effect of Exchange Bias on Magnetic Anisotropies in Fe/CoO Bilayers - Ozturk, M.; Demirci, E.; Topkaya, R.; Kazan, S.; Akdogan, N.; Obaida, M.; Westerholt, K. (Springer, 2012)
We report on the structural and magnetic properties of exchange-biased Fe/CoO bilayers grown on MgO (001) substrates by using rf-sputtering. For varying Fe thicknesses (4 nm, 10 nm, and 20 nm) the ferromagnetic resonance (FMR) spectra of bilayers have been studied as a function of temperature at X-band frequency. The resonance lines of FMR spectra have a relatively small linewidth indicating a high crystallinity of the Fe films. The room-temperature FMR data also show that the easy axis of Fe is in the film plane and parallel to the [110] crystallographic direction of MgO substrate. In addition, M versus H loops were recorded at selected temperatures by using VSM magnetometry. The VSM measurements indicate that the Fe thickness and temperature dependence of exchange-bias properties are in good agreement with the previous results on similar systems. However, the blocking temperature of the exchange-biased system is strongly reduced compared to the bulk values. This reduction in the blocking temperature is explained by both the thickness and superstoichiometric structure of antiferromagnetic CoO layer.
International Conference on Nanoscale Magnetism (ICNM) -- SEP 28-OCT 02, 2010 -- Gebze-Istanbul, TURKEY
Keywords: Exchange bias; Ferromagnetic resonance; Magnetic anisotropy; Hysteresis loops; Cobalt oxide